SSRIs versus other antidepressants for depressive disorder. - Geddes, J; Freemantle, N; Mason, J; Eccles, M; Boynton, J (2000)
OBJECTIVES: To examine the relative efficacy of selective serotonin reuptake inhibitors (SSRIs) compared to other antidepressants. SEARCH STRATEGY: The search strategy included a search of (a) Electronic bibliographic databases (MEDLINE, EMBASE); (b) reference lists of related reviews (c) reference lists of all located studies (d) contact with the manufacturer and (e) the Cochrane Group register of controlled trials SELECTION CRITERIA: Randomised controlled trials comparing selective serotonin reuptake inhibitors with other kinds of antidepressants in the treatment of patients with depressive disorders. The outcome measures assessed included measures of the severity of depression. DATA COLLECTION AND ANALYSIS: Data were collected from each study the main outcome measurefrom each study. These included: mean Hamilton depression rating scale, mean Montgomery and Asberg depression rating scale, Clinical Global Impression rating scale. An analysis of standardised mean difference of these scales was performed using Review Manager 3. 1 software. The presence of heterogeneity of treatment effect was assessed MAIN RESULTS: Ninety-eight trials contributed data to the analysis of the relative efficacy of SSRIs and related drugs with comparator antidepressants (Figure 3 and Appendix 3). Analysis of efficacy was based upon 5044 patients treated with an SSRI or related drug, and 4510 treated with an alternative antidepressant. The standardised effect size for SSRIs and related drugs together versus alternative antidepressants using a fixed effects model was 0. 035 (95% CI -0.006 to 0.076; Q = 149.25, df = 97, p < 0.001). REVIEWER'S CONCLUSIONS: There are no clinically significant differences in effectiveness between selective serotonin reuptake inhibitors and tricyclic antidepressants. Treatment decisions need to be based on considerations of relative patient acceptability, toxicity and cost.